THE DOCTRINE OF PROPRIETORSHIP. - Chow, Y. C. (The Accounting Review, 1942)
Abstract The principal concepts of the orthodox theory of proprietorship are rather vague and few of its assumptions valid under modern conditions. Much of these concepts and assumptions as resting on legalistic ideology of ownership, debt, etc., however, are unnecessary as they are undefendable. The proprietorship theory seems to be more plausible when it rests on an ownership point of view consistently applied in the analysis of business transactions and in defining cost and income. A narrow concept of owner or proprietor, however, is adapted only to the needs of calculating proprietary income and capital. It is not consistent with the more vital functions, in connection with managerial analysis, which accounting is coming to fulfill. A concept of proprietor broadly defined as the totality of private interests or the long-term investors as a class would be more logical and workable from the standpoint of theory and practice. The adoption of such a broad point of view, together with the abandon merit of any sharp distinction between proprietorship and creditorship on the basis of legal or economic ownership, no doubt changes the whole complexion and content of the orthodox theory of proprietorship; and it may be questioned whether it may still be called a proprietorship theory.